catena-Poly[[diaquanickel(II)]-bis(μ-2-{[5-(pyridin-4-yl)-1,3,4-oxadiazol-2-yl]sulfanyl}acetato)] - Gao, Ru-Qin (International Union of Crystallography, 2012)
In the title compound, [Ni(C(9)H(6)N(3)O(3)S)(2)(H(2)O)(2)](n), the Ni(II) atom, located on an inversion center, is ligated in an octahedral geometry by two carboxylate O atoms from two 2-{[5-(pyridin-4-yl)-1,3,4-oxadiazol-2-yl]sulfanyl}acetate (L) ligands and two O atoms from water molecules in the equatorial plane, and two pyridine N atoms from other two L ligands at the apical sites. Two L ligands bridge pairs of metal atoms in an antiparallel manner, forming centrosymmetric dinuclear quasi-rectangular units which are linked into infinite double-stranded chains parallel to [100]. O—H⋯O hydrogen bonds between the coordinating water molecules and the carboxylate groups of the L ligand as well as interchain S⋯N interactions [2.726 (2)–3.363 (2) Å] lead to the formation of a layer structure parallel to (001).